2000
DOI: 10.1099/00221287-146-10-2343
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic studies of dihydroxyacetone utilization in Escherichia coli

Abstract: Microbiology Comment provides a platform for readers of Microbiology to communicate their personal observations and opinions in a more informal way than through the submission of papers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 6 publications
1
20
1
Order By: Relevance
“…9). EIIA-HPr-EI Dha was purified and shown to be phosphorylated by [ 32 P]PEP in the presence of both EI and HPr but was also shown to be slightly phosphorylated in the presence of EI only (304,640). This is consistent with the absolute requirement for EI in dihydroxyacetone phosphorylation that was determined previously (376).…”
Section: Pep-dependent Dihydroxyacetone Phosphorylationsupporting
confidence: 71%
See 3 more Smart Citations
“…9). EIIA-HPr-EI Dha was purified and shown to be phosphorylated by [ 32 P]PEP in the presence of both EI and HPr but was also shown to be slightly phosphorylated in the presence of EI only (304,640). This is consistent with the absolute requirement for EI in dihydroxyacetone phosphorylation that was determined previously (376).…”
Section: Pep-dependent Dihydroxyacetone Phosphorylationsupporting
confidence: 71%
“…For E. coli, it was observed that the dha operon was induc- ible; i.e., PEP-requiring dihydroxyacetone phosphorylation activity increased when cells were grown on dihydroxyacetone (376,640). It appeared that dha operon induction is mediated by the dephosphorylation of the phosphotransfer proteins, as the inactivation of ptsI or dhaM as well as the replacement of any one of the three phosphorylatable histidyl residues in EIIA-HPr-EI Dha led to the constitutive expression of the dhaKLM operon (37).…”
Section: Pep-dependent Dihydroxyacetone Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, it appears that the PTS protein content in a bacterium correlates best with the mode of carbohydrate metabolism utilized by that organism. Bacteria that rely on anaerobic sugar metabolism via glycolysis for energy production generally have the most PTS permeases, as discussed previously (56,57). Thus, almost all bacteria that possess the PTS either are capable of anaerobic sugar utilization via glycolysis or have close bacterial relatives that are capable of such metabolism, while many of the bacteria that lack the PTS either are strict aerobes or lack a complete glycolytic cycle.…”
Section: Numbers Of Pts Protein-encoding Genesmentioning
confidence: 88%